Subcapsular liver hematoma after fibrinolytic therapy for acute myocardial infarction: a rare case report - Safi, Morteza; Khaheshi, Isa; Memaryan, Mehdi; Naderian, Mohammadreza (Acta Biomedica Atenei Parmensis, 2017)
Hemorrhagic complications of thrombolytic therapy are rare but also serious and sometimes life-threatening. Liver hematoma is a very uncommon complication following thrombolytic therapy. We present a rare case of sub-capsular liver hematoma following streptokinase therapy of acute myocardial infarction as a challenging condition. This case report highlights that emergency physicians and cardiologists should be familiar with the significant and uncommon complications of thrombolytic agents, particularly streptokinase which is used generally in under- developed countries.